Case Report: A rare synchronous multiple gastric carcinoma achieved progression-free disease through NGS-guided serial treatment - Shao, Xinyi; Yin, Jin; Wang, Di; Huang, Erjiong; Zhang, Yini; Yin, Jiani C.; Huang, Chen; Wu, Hao; Wu, Xiaoli (Frontiers in Oncology, 2023)
Synchronous multiple gastric carcinoma (SMGC) is a rare condition characterized by the simultaneous occurrence of two or more primary malignant tumors in the stomach, each with its own distinct pathological morphology. SMGC differs from gastric metastases, which originate from primary gastric or non-gastric tumors. At present, the incidence of SMGC is low in China, with no established guidelines for standard treatment. Here, we report a rare case of advanced SMGC that achieved long-lasting clinical benefits through a treatment strategy informed by next-generation sequencing (NGS). Dynamically monitoring of the tumor and/or circulating cell-free DNA guided the patient’s treatment sequentially. The patient received anti-HER2 therapy, followed by immunotherapy, pembrolizumab in combination with trastuzumab and chemotherapy, and ultimately underwent successful total gastrectomy. This case highlights a novel approach of utilizing liquid biopsy-based NGS to gain insights into disease progression and molecular response to NGS-guided treatment in SMGC patients.